Effect of environmental dust particles on laser textured yttria-stabilized zirconia surface in humid air ambient. (May 2018) - Yilbas, B.S.; Ali, H.; Al-Sharafi, A.; Al-Sulaiman, F.; Karatas, C.
Highlights: Nitride compounds formed in laser textured surfaces. Laser textured surface consists of arrays of micro/nano pillars and shows hydrophobic characteristics. Water condensates on dust particles and results in chemically active solution. Tangential force for removing dry mud from textured surface is higher than frictional force. Dried mud solution increases mud adhesion on textured zirconia surface. Abstract: Zirconium nitride is used as a selective surface for concentrated solar heating applications and one of the methods to form a zirconium nitride is texturing of zirconia surface by a high intensity laser beam under high pressure nitrogen gas environment. Laser texturing also provides hydrophobic surface characteristics via forming micro/nano pillars at the surface; however, environmental dust settlement on textured surface influences the surface characteristics significantly. In the present study, laser texturing of zirconia surface and effects of the dust particles on the textured surface in a humid air ambient are investigated. Analytical tools are used to assess the morphological changes on the laser textured surface prior and after the dust settlement in the humid air ambient. It is found that laser textured surface has hydrophobic characteristics. The mud formed during condensate of water on the dust particles alters the characteristics of the laser textured surface. The tangential force required to remove the dry mud from the textured surface remains high; in which case, the dried liquid solution at the mud-textured surface interface is responsible for the strong adhesion of the dry mud on the textured surface. The textured surface becomes hydrophilic after the dry mud was removed from the surface by a desalinated water jet.